PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA SMPN 10 PALOPO - Nurhapni Joring; Nur Saqinah Galugu; Ainul Fahmi (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to examine the effect of group counseling services using the role playing technique on improving students' learning motivation at SMPN 10 Palopo. A quantitative approach was applied with a quasi-experimental method, specifically a pretest-posttest design without a control group. The sample consisted of 15 eighth-grade students with low learning motivation, selected by purposive sampling. Data were collected using a learning motivation scale and analyzed using Paired Sample t-Test with SPSS. The results showed a significant increase in learning motivation after the intervention, with a pre-test average of 69.2 and a post-test average of 81, and a significance value of 0.000 (p < 0.05). Thus, the role playing technique is effective in enhancing students' learning motivation.